Screening the covert key using honey encryption to rule out the brute force attack of AES—a survey - Dharshini, P; Arokia Renjith, J; Mohan Kumar, P (Security and communication networks, 2016)
Recently, the major challenging attack is the side channel attack for both symmetric and asymmetric algorithm. Because in both cases, the secret key has to be sent out via a safe secured channel. The advanced encryption standard (AES) is mentioned as the best standard encryption algorithm by the US government, but there is one major attack on the AES that is the brute force attack. So, how to rule out these kinds of attack and how it is implemented effectively in hardware are being discussed in this paper. The honey encryption scheme is an effective algorithm, and it is also being discussed. In this paper, the detailed description of the AES and the methods to improve its speed and how it is integrated with the honey technique have been discussed. The different kinds of attacks and the various solutions are discussed for both of the algorithms. A survey of papers which has used these algorithms for various reasons with different perspective has been given. The honey algorithm creates the fake message for the wrong try of the key puncher. Thus, this is considered as the best algorithm, but it is also has some disadvantages that is also focussed in our survey. Copyright © 2017 John Wiley & Sons, Ltd. The above diagram shows the general architecture of how the plain text is encrypted with a honey encryption algorithm. The encrypted text is sent to the receiver node in the knowledge of the receiver. The receiver decrypts the cipher text and gets the original text without suffering from any mode of attacks.